2021
DOI: 10.1177/03635465211023758
|View full text |Cite
|
Sign up to set email alerts
|

Chondral Damage After Arthroscopic Repair Techniques for Acute Bony Bankart Lesions: A Biomechanical Study

Abstract: Background: Bony Bankart lesions can be encountered during treatment of shoulder instability. Current arthroscopic bony Bankart repair techniques involve intra-articular suture placement, but the effect of these repair techniques on the integrity of the humeral head articular surface warrants further investigation. Purpose: To quantify the degree of humeral head articular cartilage damage secondary to current arthroscopic bony Bankart repair techniques in a cadaveric model. Study Design: Controlled laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…If left untreated, this lesion can cause recurrent instability 1 , 6 , 7 and may lead to early degenerative changes in the glenohumeral joint. 3 , 8 , 9 , 10 Osteochondral fracture can be treated with various treatment options, including debridement, structural repair, screws fixation, microfracture, bone grafting, and arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, this lesion can cause recurrent instability 1 , 6 , 7 and may lead to early degenerative changes in the glenohumeral joint. 3 , 8 , 9 , 10 Osteochondral fracture can be treated with various treatment options, including debridement, structural repair, screws fixation, microfracture, bone grafting, and arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Nakawaga et al found that placing multiple soft suture anchors in a linear arrangement for Bankart repairs might be associated with postoperative recurrence of instability due to new glenoid fractures along the suture anchor insertion sites [16]. In addition, Greenstein et al demonstrated in a cadaveric model that placement of intraarticular sutures during arthroscopic bony Bankart repair techniques may harm the humeral head cartilage and suggested further investigation of alternative, cartilage-sparing arthroscopic techniques for anterior glenoid fractures [9]. All these arthroscopic methods have in common that the implants are drilled and placed from anteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the linear placement of anchors has been reported to be associated with secondary fractures of the glenoid or irritation Fig. 2 8 With the anterior edge of the anterior fragment under the hook, the two bullets are placed on the scapula neck over the glenoid guide through an additional posteromedial skin incision of the joint due to non-absorbable sutures [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Zu beachten bei dieser Art der Fixierung ist jedoch die hiermit verbundene intraartikuläre Lage des Fadenmaterials. Da dieses in aller Regel sehr stabil und nicht resorbierbar ist, ist nicht verwunderlich, dass dies in der biomechanischen Untersuchung von Greenstein et al zu Knorpelschäden im Bereich des Humeruskopfes führt[24]. Eine tatsächlich deutlich höhere Rate an posttraumatischer Arthrose ist aufgrund der fehlenden Daten für diese Techniken im Vergleich zu anderen Techniken noch nicht bekannt.Bei schweren nicht rekonstruierbaren Frakturen muss grundsätzlich ein struktureller Glenoidaufbau mit Becken-kammspan, Korakoidtransfer oder allogenem Knochen erwogen werden.…”
unclassified